Hour‐specific nomogram for transcutaneous bilirubin in Japanese neonates. Issue 5 (21st August 2013) - Kuboi, Toru; Kusaka, Takashi; Kawada, Koh; Koyano, Kousuke; Nakamura, Shinji; Okubo, Kensuke; Yasuda, Saneyuki; Isobe, Kenichi; Itoh, Susumu
Abstract Background The measurement of transcutaneous bilirubin (TcB) is very important to screen for hyperbilirubinemia in newborns. Until now, however, there has been no hour‐specific, percentile‐based TcB nomogram during the early neonatal period in Japanese neonates. The aim of this study was to develop a TcB nomogram within 72 h of birth in Japanese neonates. Methods A total of 3152 TcB measurements for 181 healthy Japanese neonates (gestational age ≥36 weeks, birthweight ≥2300 g) were obtained within 72 h of birth. All measurements were performed with a Konica Minolta jaundice meter, the JM‐103. A nomogram curve was plotted to show the trend of TcB level over time. Results The nomogram curves rose almost linearly for all percentiles until 72 h after birth. Conclusion An hour‐specific, percentile‐based TcB nomogram during the first 72 h after birth in Japanese neonates was successfully developed. Because Japanese neonates have higher and later peak bilirubin, an original hour‐specific 97.5th percentile‐based TcB nomogram may be needed to identify early‐onset jaundice and manage neonatal hyperbilirubinemia.